Conway's Demonstration of a Mediator Between God and Creatures - Douglas Bertrand Marshall (Journal of Modern Philosophy)
In her sole philosophical treatise, The Principles of the Most Ancient and Modern Philosophy, Anne Conway (1631-1679) offers a demonstration of the proposition that, in addition to God and creatures, there is a being whose essence is the medium between God’s essence and creatures’ essence. We offer an interpretation of Conway’s demonstration that reveals its dependence on a rational principle ('PME'): if beings with extreme natures are united, then they are united by means of a being whose nature is the medium between the extremes. We also assess the extent to which Conway offers a justification for her metaphysics by demonstrating her claims from principles known by the understanding. Conway’s philosophical demonstrations are suggestive of a rationalist position on which her metaphysics may be proved from a small number of propositions established independent of experience. However, we ultimately argue that Conway’s philosophical methodology is not rationalist in this sense: for Conway is willing to take our daily experience as the evidence for a metaphysical principle, and also to argue for her philosophy on the basis of a consensus among authoritative texts.